Les nouveaux contours du champ intellectuel musulman en France - Franck Fregosi (Revue des Mondes Musulmans et de la Méditerranée)
Islam in France hides a heterogeneous human reality which is quite removed from the stereotypes and clichés that generally abound about it. This is also true of the French Muslim intellectual landscape, a competitive space, in which diverse actors hold distinct and often opposing visions and representations of Islam, confront each other and strive nevertheless to present their Islam as the socially legitimized version that is compatible with the surrounding society. This article attempts to delimit the boundaries of the Muslim intellectual field by studying its dynamics and by proposing a typology of French Muslim intellectuals.